Nanointerface‐Driven Reversible Hydrogen Storage in the Nanoconfined Li–N–H System. Issue 3 (20th January 2017) - Wood, Brandon C.; Stavila, Vitalie; Poonyayant, Natchapol; Heo, Tae Wook; Ray, Keith G.; Klebanoff, Leonard E.; Udovic, Terrence J.; Lee, Jonathan R. I.; Angboonpong, Natee; Sugar, Joshua D.; Pakawatpanurut, Pasit
Abstract : Internal interfaces in the Li3 N/[LiNH2 + 2LiH] solid‐state hydrogen storage system alter the hydrogenation and dehydrogenation reaction pathways upon nanosizing, suppressing undesirable intermediate phases to dramatically improve kinetics and reversibility. The key role of solid interfaces in determining thermodynamics and kinetics suggests a new paradigm for optimizing complex hydrides for solid‐state hydrogen storage by engineering internal microstructure.